ANALISIS FLYPAPER EFFECT DAN KEMAMPUAN KEUANGAN DAERAH DI KABUPATEN/KOTA SUMATERA BARAT - Della Jesika; Alpon Satrianto (Universitas Negeri Padang, 2019)
This study aims to determine whether there is an influence bettwen PAD, DAU, DBH, DAK on Regional Expenditure in the District/City of West Sumatra. This study also analyzed whether there was a flypaper effect in West Sumatra an how the condition of reginal financial capabilities in teh District/City of West Sumatra. The data used are secondary data in the form of panels with a period of time from 2015 to 2017, with the technique of collectting documentation data and libarary studies obtained from relevant intitusions and agencies. The variabels used are Reginal Expenditures, PAD, DAU, DBH, and DAK. The research method used is the Panel Regression Model and the Quadrant Mwthod. The results show that: (1) there is a positive and significant relationship between PAD and Regional Expenditure (2) there is a posotive and significant relationship between DAU and Regional Expenditure (3) there is a negative and insignificant relationship between DBH and Regional Expenditure (4) there is a positive and significant relationship between DAK of Regional Expenditure (5) inicated a flypaper effect in West Sumatra (6) from 19 District/City in west sumatra, only 5 regions occupying qudran I, 4 regions occupying qudran II, one occupying qudran III and 9 regions occupy qudran IV.